Power sharing conditioning control in single-phase parallel distributed generations with simple improvement of droop control - Jackson, Ronald (2019)
Droop control is the critical solution for sharing the power demand between Distributed Generations (DGs) in islanding microgrid when there is no support from the electricity distribution grid. The droop control is applied as the local control scheme to achieve power sharing among parallel inverters with DG sources. As it has been well established, this control strategy is combined frequency and voltage droop method. In droop strategy, the voltage and frequency are drooped to a new rated value to ensure power load sharing. Therefore this project to have an improvement of the droop under self-frequency restoration method is adopted in order to obtain accurate power sharing and fast frequency tracking capability with better load sharing between parallel DGs are been conducted in this project. It is where the improved droop control is used to have faster restoration for the voltage and frequency to nominal values within a limited time and to ensure the proper power sharing between the DGs considering based on the rating of energy source. The performance of the proposed controller is implemented in MATLAB/Simulink software and compared by two simulation tests under two exigent load circumstances as well also as through the connection of DGs to the point of common coupling (PCC). It is to verify the proposed control model has capability to response accurately during the power transient and power sharing conditions at both DGs. In proportion, the implementation of frequency restoration loop to the improved droop control has create a condition where it knows as an autonomous smart grid system whereby the restoration of the frequency and voltage can be done automatically. As a result, the improved controller can achieve better steady-state performance and fast restoration tracking speed within 3.5ms with 2.8ms rise time as compared to 8.5ms rise time for the conventional droop control. It also reduces the overshoot during the load transient to 4% and increases the tracking efficiency by 90% as compared to the 40% overshoot and 85% efficiency for the conventional control. Hence, the autonomous smart microgrid system is successfully presented under this proposed controller along with accurate power sharing performance between DGs and fast frequency restoration.